SUBSTRATE-MODE HOLOGRAPHIC POLARIZATION-DIVISION MULTI/DEMULTIPLEXER FOR OPTICAL COMMUNICATIONS - CHANG, JT; SU, DC; HUANG, YT (My University, 1994)
Based on the diffractive properties of a transmission-type phase volume hologram, a new type of polarization-division multi/demultiplexer for optical communications is presented.